Starost na Zemi po humanismu - Ritter, Martin (Filosoﬁcký časopis)
The primary aim of the article is to present posthumanism as an approach needed in the era of the Anthropocene. By posthumanism, I mean a way of thinking that overcomes the weaknesses of humanism and emphasizes the essential interconnectedness of human beings with their environment. With regard to this “ecological” dimension of posthumanism, I will focus on the relationship between humans and technology, drawing on Bernard Stiegler. Stiegler’s reflections show that in the era of the Anthropocene human beings have become an irrational force that pulls the rest of the living beings into a spiral of destruction through the technological system they have established in the shared terrestrial environment. This environment is an organ of the planetarily influential and at the same time planetarily dependent humanity, which must therefore assume responsibility for the Earth.